Acknowledgments, Dairy Research 2016 - B. Bradford (Kansas Agricultural Experiment Station Research Reports, 2016)
Appreciation is expressed to the following organizations for their support of dairy teaching, research, and extension at Kansas State University during 2015-2016.
Keywords: Dairy research